Karakteristik kimiawi air danau kawah Gunung Api Kelud, Jawa Timur pasca letusan tahun 1990 - Kadarsetia, Eka; Primulyana, Sofyan; Sitinjak, Pretina; Saing, Ugan Boyson (Indonesian Journal on Geoscience, 2006)
http://dx.doi.org/10.17014/ijog.vol1no4.20062Kelud is a strato type volcano characterized by phreatomagmatic and magmatic eruptions. Since last eruption in 1990, the volcano has showed no-more signifi cant volcanism. Currently, there is an opened westward crater lake as a remained eruption crater containing meteoric water and volcanic gases condensate generated from subsurface.Analysis result of lake water exhibits that its chemical composition was fl uctuated due to an infl uence of factors such as seasons, rates of volcanism activity and reactivity of internal chemical elements within the lake water.The volume of lake water increases during the wet season and experiences dilution to make declination of chemical components within the water. Temperature of the lake water increases as well as volcanic intensity, simultaneously to make addition of dissolved chemical compounds and elements such as SO , Cl, B, and F and creates acidic water. Fumarole/solfatara released anykind of gases, such as H O, CO , CO, HCl, SO , H S, HF, H , HBr, NH , CH , H BO , and N . Moreover interaction of andesitic rock and acidic water apparently produces ionic source of Na, K, Ca. Mg, Fe, Al including trace elements such as Zn, Li, Sr, As, Rb, Cr, Pb, Ti, Ni, Cu, Ce, and Be.The composition of crater lake water of the Kelud volcano is included into an immature water category with HCO . The fl uctuation of element, compound and gas contents within the lake water with their depletion trend during the period of 1990 â 2005 may be related to decreasing of volcanism activity in the duration of 1990 post-eruption.Â